2023
DOI: 10.1021/acs.est.2c08891
|View full text |Cite
|
Sign up to set email alerts
|

Simple Management Changes Drastically Reduce Pig House Methane Emission in Combined Experimental and Modeling Study

Abstract: Reducing methane from livestock slurry is one of the quickest ways to counteract global warming. A straightforward strategy is to reduce slurry retention time inside pig houses by frequent transfer to outside storages, where temperature and therefore microbial activity are lower. We demonstrate three frequent slurry removal strategies in pig houses in a year-round continuous measurement campaign. Slurry funnels, slurry trays, and weekly flushing reduced slurry methane emission by 89, 81, and 53%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Particularly propionic acid concentrations >900 mg L −1 are inhibitory for methanogenic activity (Wang et al, 2009), and propionic acid exceeded ∼1.5 g L −1 throughout the incubation experiments at 10-15˚C and until day 63 at 20-25˚C. Similar or higher concentrations of VFA and propionic acid are normally observed in pig slurry (Dalby et al, 2023;Sommer et al, 2015). After ∼2, ∼5, and ∼10 weeks, CH 4 emission increased at 20˚C, 15˚C, and 10˚C, respectively (ρ = 0.3 for time-CH 4 production rate at all temperatures), but not at a rate comparable to that observed at 25˚C after 1 week (ρ = 0.37 for temp-CH 4 production rate).…”
Section: Methane Emission and Methanogenic Communitymentioning
confidence: 75%
See 3 more Smart Citations
“…Particularly propionic acid concentrations >900 mg L −1 are inhibitory for methanogenic activity (Wang et al, 2009), and propionic acid exceeded ∼1.5 g L −1 throughout the incubation experiments at 10-15˚C and until day 63 at 20-25˚C. Similar or higher concentrations of VFA and propionic acid are normally observed in pig slurry (Dalby et al, 2023;Sommer et al, 2015). After ∼2, ∼5, and ∼10 weeks, CH 4 emission increased at 20˚C, 15˚C, and 10˚C, respectively (ρ = 0.3 for time-CH 4 production rate at all temperatures), but not at a rate comparable to that observed at 25˚C after 1 week (ρ = 0.37 for temp-CH 4 production rate).…”
Section: Methane Emission and Methanogenic Communitymentioning
confidence: 75%
“…It was suggested that degradable VS could be quantified in an aerobic assay (Petersen et al., 2016), but the method is tedious and does not address the fact that degradable VS consists of many OM sub‐pools that may degrade at completely different rates. At low temperatures, methanogenesis can be rate limiting (Dalby et al., 2023), necessitating modeling of microbial growth for the prediction of CH 4 emission in slurries at farms. The anaerobic biodegradation model includes the growth of methanogen groups but does not differentiate between VS sub‐pools due to limited knowledge of hydrolysis rates at low temperatures (Dalby et al., 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the identified list of best practices is not exhaustive, while the successful control and reduction in GHGEs depend on many factors. For example, academic research highlights the role of animal genetics [48], age and weight [16,34], activity and density [16,42], climate characteristics and season [16,45], building characteristics, including equipment, such as ventilation [16,49], frequency of manure/slurry removal from buildings [39,50], storage practices [46], emissions that depend on the particular manure utilisation techniques [15,46,51], etc. In fact, the GHGE potential in MSs depends on the multi-choice options on farms, and research that covers the aforementioned aspects and assists in the selection of the most effective and economically viable GHGE reduction alternatives remains critical for the development of sustainable pig farming systems.…”
Section: Ghge Reduction Alternativesmentioning
confidence: 99%